VL Sabji Matar 14: New garden pea(Pisum sativum var. hortense)cultivar with resistance to powdery mildew - Hedau, N K; G V, Chaudhari; Ram, Hanuman; Pandey, B M (Indian Horticulture, 2025)
VL Sabji Matar 14 (Pisum sativum L. var. hortense) is a new garden pea cultivar released for Agro-ecological Zone I (Uttarakhand), India. The cultivar was developed through hybridization between PC 531 and Pusa Pragati, followed by selection using the pedigree method. It belongs to the medium-maturity group and is resistant to powdery mildew. Additionally, it exhibits resistance to white rot, wilt, and leaf blight under field conditions and shows lower incidence of pests such as pod borer in mid-hill regions. The cultivar produces attractive, long, curved green pods—preferred by consumers—with 10–12 seeds per pod and a high shelling percentage (>50%). The average green pod yield ranges from 11 to 12.5 t/ha. VL Sabji Matar 14 is suitable for cultivation under both organic and inorganic production systems.